GIS and spatial database in soil mapping - Курілов, В. І. (Man and Environment. Issues of Neoecology)
Spatial databases management system significantly enhances the efficiency and productivity of GIS, working as a database interface and tool for analyzing spatial information. Therefore, they are so important for soil mapping. By the local example (Kharkiv region) developed a technique of creating a spatial database to needs of soil-erosion survey of area. An approach to automate the process of field description of soil profiles are proposition.